PENGARUH POTENSI DIRI DAN LINGKUNGANSOSIAL TERHADAP MINAT MELANJUTKANPENDIDIKAN KE PERGURUANTINGGI PADA SISWA SMA NEGERI 1 KARANGGEDE BOYOLALI TAHUN AJARAN 2017/2018 - -, Khoirul Janah -; -, Mintasih Indriayu -; -, Sudarno - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The aims of this research are 1) to know the impact between self-potency and social environment to the interest to continuing education into the college on students of SMA Negeri 1 Karanggede Boyolali Academic Year of 2017/2018, 2) to know the impact of self-potency to the interest of continuing study into the college on students of SMA Negeri Karanggede Boyolali Academic Year of 2017/2018, 3) to know the impact of social to the interest of continuing study to the college on students of SMA Negeri Karanggede Boyolali Academic Year of 2017/2018. Sampling technique used in this research was Proportional Random Sampling. The total number of sample was 240 respondents. Data collecting technique used was questionnaire and documentation. Analysis data technique used was multiple linear regression. The result shows multiple linear regression obtained Y= 15,662 + 0,467 X1 + 0,380 X2, regression coefficient is positive and significant which means that self-potency gives positive impact to the interest of continuing study into the college. Moreover, it shows that social environment gives positive and significant impact on the interest of continuing study into the college. It means that stronger self-potency on each student will lead to bigger interest to continue study to the college. Based on the result, it can be concluded (1) both self-potency and social environment affect the interest on continuing study to the college with <0,05 (0,000<0,05) probability, (2) self-potency affect to the interest on continuing study to the college with <0,05 (0,000<0,05) probability, (3) social environment gives impact to the interest of continuing study to the college with <0,05 (0,000<0,05) probability, and 55,1% R square. This shows 55,1% of interest on continuing study into college was affected by both self-potency and social environment while the rest of 44,9% was affected by other factors that unexplained in this research.